Comparative effects of soil and water salinity on oil quality parameters of Brassica juncea - Jogendra Singh; PC Sharma (Journal of Oilseed Brassica, 2026)
Effect of soil and water salinity on oil quality of Indian mustard was evaluated. Based on germination test,five salt tolerant genotypes were selected out of 26 at seedling stage and used for field study. Pot experimentwas carried out on two crop seasons under three salinity levels of irrigation water (ECiw Control, 12 and 15dS/m) while field experiment was conducted under three saline environments viz. Control, ECe 9 and 12 dS/m. Soil salinity was monitored over the entire crop cycle. Harvested seeds were subjected to seed analysisfor oil, protein, erucic acid and crude fiber content using a pre-standardized Fourier Transform Near InfraredReflectance Spectrometer. Under increasing salinity (water and soil); oil, protein and crude fibre contentdecreased, 7-10%; 18-19% and 36-42%, respectively, while erucic acid content increased by 30-42% comparedto control. The reductions and increments varied for different genotypes. Comparative study of salinity in potand field showed that soil salinity at ECe 9 dS/m have similar effect, as water salinity at ECiw 12 dS/m overthe oil and quality parameters in mustard. Consideration was given in this experiment to determineappropriate breeding strategies for screening and development of superior oil quality genotypes under salinityconditions.